Basic concepts and current developments of Latvian administrative law - Danovskis, Edvins (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The article outlines some basic elements of Latvian administrative law, namely the civil service system, state liability law and administrative offence law. The Latvian civil service system is characterized as a decentralized position model, and concepts of “decentralization” and “position” model are briefly described. In the context of state liability law a recent development of the introduction of the concept of “non-material harm” is outlined, explaining why Latvian administrative law has abandoned the concept of “moral harm” used previously. Regarding administrative offence law the article describes the most significant changes to be introduced into legislation in 2018
Keywords: łotewskie prawo administracyjne; służba cywilna; odpowiedzialność państwa; wykroczenia administracyjne